Existence and uniqueness of global classical solutions to a two dimensional two species cancer invasion haptotaxis model - Giesselmann, Jan; Sfakianakis, Nikolaos (Discrete and continuous dynamical systems, 2018)
We consider a haptotaxis cancer invasion model that includes two families of cancer cells. Both families migrate on the extracellular matrix and proliferate. Moreover the model describes an epithelial-to-mesenchymal-like transition between the two families, as well as a degradation and a self-reconstruction process of the extracellular matrix. We prove in two dimensional space positivity and conditional global existence and uniqueness of the classical solutions of the problem for large initial data.